Cerium Oxide Applications and Attributes - Bahadar Khan, Sher; Akhtar, Kalsoom (IntechOpen, 2019)
This book focuses on the chemical structure and applications of CeO2. It covers the recent developments in a wide range of CeO2 applications, particularly catalysis corrosion protection, fuel cells, sensors, and UV-blocking. It also provides a concise but thorough coverage of the chemical structure and applications of CeO2. Thus, this book provides an overview of chemical structure, applications, and recent attributes of CeO2 for a broad audience, including beginners, graduate students, and specialists in both academic and industrial sectors.